SUD MENNUCCI – EDUCADOR PAULISTA: PORQUE ESTUDÁ-LO HOJE? (Revista Labor, 2017)
SUD MENNUCCI – PAULISTA EDUCATOR: WHY STUDYING  IT TODAY?Resumo O estudo e a preservação da memória de educadores paulistas são relevantes no sentido de fornecer subsídios para a discussão sobre as contribuições teóricas e práticas destes educadores na história da educação brasileira. Ressalta-se que muitos destes ainda são pouco conhecidos no cenário acadêmico, sobretudo nas pesquisas e produções realizadas nos programas de stricto sensu em educação no estado de São Paulo. Aqui pretendemos destacar a importância de Sud Mennucci para elucidar os problemas da educação brasileira e do ensino rural, sobretudo no contexto da década de 1930.Abstract The study and preservation of the memory of educators from the state of São Paulo (paulista educators) are relevant in order to provide subsidies for the discussion about the theoretical and practical contributions of these educators in the history of Brazilian education. It should be noted that many of these are still little known in the academic scene, especially in the research and productions carried out in stricto sensu programs in education in the state of São Paulo. Here we want to highlight the importance of Sud Mennucci to elucidate the problems of Brazilian education and rural education, especially in the context of the 1930s.Keywords: Sud Mennucci – Paulista educator - Rural education – The history of Brazilian Education – New School